Cedilanid inhibits retinal neovascularization in a mouse model of oxygen-induced retinopathy - Zhang, Jing Shang; Jonas, Jost B. (Molecular vision, 2017)
PURPOSE: This study investigated the effect of cedilanid on retinal neovascularization in a mouse model of oxygen-induced retinopathy. - METHODS: Seven-day-old C57BL/6 mice were exposed to 75% ± 1% oxygen for 5 days and were then returned to room air to induce retinal neovascularization. Cedilanid (0.025-0.2 μg) was intravitreally injected into the left eye of each mouse on postnatal day 12 (P12) and P15. PBS was intravitreally injected into the right eye as a control. Retinal neovascularization was evaluated with isolectin GS-IB4 staining of the retinal blood vessels. The function of reestablishment blood vessels was evaluated with angiography with the injection of fluorescein isothiocyanate (FITC)-dextran followed by isolectin GS-IB4 staining. Real time (RT)-PCR and western blot were used to examine the mRNA and protein expression of hypoxia inducible factor 1 alpha (HIF-1α) and vascular endothelial growth factor (VEGF), respectively. - RESULTS: Retinal neovascular areas and obliterative areas were statistically significantly smaller in the eyes injected with cedilanid (0.05 μg, 0.1 μg, and 0.2 μg) compared with the control eyes. The inhibitory effect of cedilanid was observed in a dose-dependent manner. In addition, the retinal neovascular areas and the obliterative areas in the eyes injected with 0.2 μg cedilanid on P12 were statistically significantly smaller than those in the eyes injected with the same dose of cedilanid on P15. Cedilanid promoted the circulative function of reestablished blood vessels in the obliterative areas. Cedilanid inhibited the expression of HIF-1α and VEGF in mice treated with hyperoxia. - CONCLUSIONS: Cedilanid inhibits retinal neovascularization in a mouse model of oxygen-induced retinopathy. Early treatment with cedilanid produces better inhibition of retinal neovascularization. Cedilanid may be a potential treatment of neovascular diseases.
Gesehen am 31.07.2018